Moderasi Beragama Dalam Bingkai Pendidikan Agama Kristen Kehidupan - Semuel Selanno (Jurnal Ilmiah Wahana Pendidikan, 2022)
There are several articles that talk about religious moderation and Christian Religious Education. The uniqueness of this paper lies in the relationship between religious moderation and Christian Religious Education (PAK) of Life. That religious moderation as an approach to religion is very much needed in the context of religious pluralism. The religious way of a multi-religious society requires a moderate attitude that is framed in the PAK of Life. PAK of life as an entry point for the development of religious moderation. The purpose of this paper is to show an urgent need for religious moderation as a moderating social and religious pedagogical capital for a harmonious life through PAK Life. There are three things that are emphasized through this paper, namely; moderate religious literacy; PAK Life and the Role of PAK Life in religious moderation. The method used in this paper is a qualitative method through literature study